Development of helium electron cyclotron wall conditioning on TCV. (22nd December 2017) - Douai, D.; Goodman, T.; Isayama, A.; Fukumoto, M.; Wauters, T.; Sozzi, C.; Coda, S.; Blanchard, P.; Figini, L.; Garavaglia, S.; Miyata, Y.; Moro, A.; et al.
Abstract: JT-60SA envisions electron cyclotron wall conditioning (ECWC), as wall conditioning method in the presence of the toroidal field to control fuel and impurity recycling and to improve plasma performance and reproducibility. This paper reports on Helium ECWC experiments on TCV in support of JT-60SA operation. Nearly sixty Helium conditioning discharges have been successfully produced in TCV, at a toroidal field B T = 1.3 or 1.54 T, with gyrotrons at 82.7 GHz in X2 mode, mimicking ECWC operation in JT-60SA at the second harmonic of the EC wave. Discharge parameters were tuned in order to (i) minimize the time for the onset of ECWC plasmas, thus minimizing absorption of stray radiation by in-vessel components, (ii) improve discharge homogeneity by extending the discharge vertically and radially, and wall coverage, in particular of inboard surfaces where JT-60SA plasmas will be initiated, (iii) assess the efficiency of He-ECWC to deplete carbon walls from fuel. An optimized combination of vertical and radial magnetic fields, with amplitudes typically 0.1 to 0.6% of that of B T, has been determined, which resulted in lowest breakdown time, improved wall coverage and enhanced fuel removal. A standard ohmic D 2 -plasma could be then sustained, whereas it would not have been possible without He-ECWC.